Evaluating the circadian rhythm and response to glucose addition in dispersed growth cultures of Neurospora crassa. Issue 5 (May 2020) - Kelliher, Christina M.; Loros, Jennifer J.; Dunlap, Jay C.
Abstract: Work on the filamentous fungus Neurospora crassa has contributed to or pioneered many aspects of research on circadian clock mechanism, a process that is functionally conserved across eukaryotes. Biochemical assays of the fungal circadian clock typically involve growth in liquid medium where Neurospora forms a spherical ball of submerged mycelium. Here, we revive a method for dispersed growth of Neurospora in batch culture using polyacrylic acid as an additive to the medium. We demonstrate that dispersed growth cultures utilize more carbon than mycelial balls, but nonetheless retain a functional circadian clock. This culturing method is suited for use in circadian experiments where uniform exposure to nutrients and/or increased biomass is required.